PENGARUH KOMPOSIT SERAT IJUK PADA PLAT GALVANIS TERHADAP KEKUATAN TARIK DAN MIKROSTUKTUR - M. Miftakhul Ulum Rizal; M. Effendi (Prodi Teknik Mesin Universitas Yudharta, 2020)
The use of natural fibers, such as fibers, can be used as an innovative material. The fibers are elastic, hard, water resistant, and difficult to digest by destructive organisms. Natural fibers are very environmentally friendly because they can be degraded naturally and the price of natural fibers is cheaper than synthetic fibers. This study aims to determine the effect of composite fibers and galvanies steel (zinc) on tensile strength and to determine the effect of composite fibers and galvanies steel (zinc) on the microstructure. The results of this study the tensile strength made from galvanies (Zn) has a high tensile strength value of 122.6 Kg/mm2 with a low stress value of 8.3%, so that the galvanies plate has ductile properties, the material of Galvanies (Zn) and fibers with fibers. A thickness of 2 mm after the tensile test has a tensile stress of 21.4 Kg/mm2 and a strain of 11.8%, the size of the pieces of the fibers can affect the tensile strength, and the material of Galvanies (Zn) and fibers with a thickness of 3 mm after performed a tensile test having a tensile strength of 20.4 Kg/mm2 and a strain of 16.2%.